Myolipoma of Mesentery: A Case Report. (30th December 2013) - Kim, Hyun Sung; Kim, Suk; Kim, Kyungbin; Choi, Kyung Un; Kim, Joo Youn
Abstract : Myolipomas are very rare benign lipomatous soft tissue tumors which are usually located in retroperitoneum, abdominal and pelvic cavity, and the abdominal wall. They can be diagnosed histologically by the presence of irregularly admixed mature adipose tissue and smooth muscle fibers. The correct diagnosis of myolipoma is important, because it should be considered in the differential diagnosis of fat-containing lesions of the soft tissue and should follow a benign clinical course despite its frequently large size and deep location. We report here a case of myolipoma arising in the mesentery of the jejunum.